2002
DOI: 10.1271/bbb.66.1713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Medium-Chain Triacylglycerols on Serum Lipoproteins and Biochemical Parameters in Healthy Men

Abstract: The objective of this study was to investigate eŠects of dietary medium-chain triacylglycerols (MCTs) on serum lipid levels, liver function, and hepatic fat accumulations in healthy men. Eleven subjects consumed 2200-2600 kcal daily, of which 70-80 g was fat; the fat included 40 g of MCTs or else 40 g of long-chain triacylglycerols (blended vegetable oil). The diet was followed for 4 weeks in this controlled double-blind study. At the end of the experiment, signiˆcant diŠerences were not found in the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
20
1
3
Order By: Relevance
“…In a controlled double-blind study, Nosaka et al (2002) found that serum TG levels of healthy subjects were not significantly different in the groups consuming 2200-2600 kcal daily for 4 weeks, of which 70-80 g was fat; the fat included 40 g of MCT or else 40 g of LCT.…”
Section: Discussionmentioning
confidence: 97%
“…In a controlled double-blind study, Nosaka et al (2002) found that serum TG levels of healthy subjects were not significantly different in the groups consuming 2200-2600 kcal daily for 4 weeks, of which 70-80 g was fat; the fat included 40 g of MCT or else 40 g of LCT.…”
Section: Discussionmentioning
confidence: 97%
“…14,19,20) In addition, MCFAs was also found to lower blood TG. 14,[17][18][19][20] Moreover, apolipoprotein profiles in the blood were also improved greatly in Chinese hypertriglycerideamic subjects. 22) In the present study, we found that MLCT lowered body weight and body fat weight only in the hypertriglycerideamic subjects of age less than 60 years, not in those more than 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have found negative effects of MCFAs on blood TG. 14,[17][18][19][20] On the contrary, some have reported a positive role of MCFAs in lowering blood TG. 8,21) We have reported that MLCT reduced blood TG in Chinese hypertriglycerideamic subjects.…”
mentioning
confidence: 99%
“…In the current cohort of animals, we similarly observed that hepatic lipid accumulation was increased after LCFA feeding, and to an even greater extent after MCFA feeding (data not shown). While excess hepatic lipid can have deleterious metabolic effects, it should be noted that many studies in rodents and humans have reported no adverse effects of MCFAs on liver lipid levels ( 4,26,33,34 ). These disparate fi ndings on liver lipid accumulation between studies indicates that differences in methodological factors may also be important, such as the exact composition and fat content of the MCFA-enriched diets, as well as the composition of the other macronutrients in the diet.…”
Section: Effect Of Dietary Mcfa and Lcfa Intake On Protein Expressionmentioning
confidence: 99%